The patients‘ perspective - a qualitative analysis of experiencing a fracture-related infection - Wimalan, Bravena; Rupp, Markus; Alt, Volker; Walter, Nike (Frontiers in Psychology, 2023)
Introduction: Fracture-related infection is a devastating complication confronting the patient with several challenges. To improve the management and to enhance the patients’ wellbeing the focus of this study was to understand the emotional impact and patients’ experiences during the process to identify challenges, difficulties, and resources. Method: In total 20 patients of a German university orthopaedic trauma centre specialized on bone and joint infections were recruited using a purposive sampling strategy. Content analysis was performed on transcripts of individual in-person interviews with patients treated at the hospital between 2018 and 2021. Results: The following major themes emerged: (i) the emotional and mental aspects highlighting the fact that FRI patients faced severe restrictions in their day-to-day life, which resulted in dependency on others and frustration, as well as future concerns showing that patients could not overcome a state of anxiety and fear even after successful treatment. (ii) Socioeconomic consequences confronting patients with consequences on the job and in finances where they often feel helpless, and (iii) resources emphasizing the role of spirituality as a coping strategy and yoga exercises for keeping the positivity. Conclusion: This study emphasized the challenge of fracture-related infection management and associated consequences from the patients’ perspective. Not being well informed about possible negative outcomes or restrictions makes it harder for patients to accept the situation and patients expressed a need for better information and certainty. Also, patients developed constant anxiety and other psychological disturbances, highlighting the potential benefit of psychological support and patient-peer support to exchange experiences.